PENGARUH KEPATUHAN KODE ETIK AUDITOR TERHADAP EFEKTIVITAS PROSES AUDIT - Aditya Risky Mahendra; Muhammad Iqbal Ainur Rahman; Tries Ellia Sandari (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the influence of auditors’ compliance with the professional code of ethics in improving the effectiveness of the audit process. Compliance with the principles of integrity, objectivity, professional competence, confidentiality, and professional behavior is a fundamental aspect that serves as the main guideline for conducting a high-quality audit. Various studies in Indonesia indicate that auditors who adhere to the code of ethics tend to produce more structured audit processes, are better able to identify risks accurately, and generate more reliable reports. Based on this foundation, this study employs a quantitative approach through surveys of external and internal auditors to determine the extent to which ethical compliance affects audit effectiveness. The analysis is conducted using linear regression to assess the relationship between these variables. The results show that compliance with the code of ethics has a positive and significant effect on the effectiveness of the audit process, particularly in the stages of planning, performing audit procedures, and preparing reports. These findings emphasize that the implementation of the code of ethics is not only a professional requirement but also a key factor that determines the overall success of the audit process and strengthens the quality of decision-making in audit practice.